2019
DOI: 10.1002/jper.18-0748
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 mediates alveolar bone resorption in experimental peri‐implantitis through regulation of CD45+ cell infiltration, RANKL/OPG ratio, and inflammatory cytokine production

Abstract: Background:The present study was to determine the role of Toll-like receptor 4 (TLR4) signaling in inflammation and alveolar bone resorption using a murine model of Porphyromonas gingivalis-associated ligature-induced peri-implantitis. Methods:Smooth surface titanium implants were placed in the left maxilla alveolar bone 6 weeks after extraction of first and second molars in Wild-type (WT) and TLR4 −/− (TLR4 KO) mice. Silk ligatures immersed with P. gingivalis were tied around the implants 4 weeks after the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 34 publications
1
17
0
2
Order By: Relevance
“…Comparing dental and orthopaedic implant loosening processes overlaps in cellular components and their gene expression patterns, which refer to the same triggers and result in similar mechanisms, influencing the induction of osteoclastogenesis within peri-implant tissues of both types, have been discussed. Especially the (immune) regulatory effects of dental and orthopaedic PPFs, which play a major role in implant loosening, have been described in literature (10,11,14,18,23,24,(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Comparing dental and orthopaedic implant loosening processes overlaps in cellular components and their gene expression patterns, which refer to the same triggers and result in similar mechanisms, influencing the induction of osteoclastogenesis within peri-implant tissues of both types, have been discussed. Especially the (immune) regulatory effects of dental and orthopaedic PPFs, which play a major role in implant loosening, have been described in literature (10,11,14,18,23,24,(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al [ 38 ] found that TLR4 signaling may mediate inflammation and bone resorption in peri-implantitis through the regulation of B cell infiltration, the RANKL/OPG ratio, and differential inflammatory cytokine production. Previous studies have shown that the anti-inflammatory microRNA miR-146a enhances the inhibition of peri-implant bone resorption through the regulation of TLR2/4 signaling [ 39 ] and Wnt5a involved in TLR4 signaling induces the production of inflammatory cytokines and causes breakdown of extracellular matrix in peri-implantitis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mice were given sulfamethoxazole and trimethoprim (850 μg/170 μg/mL) in the drinking water for 2 weeks. Six weeks later, implants were placed in all animals as previously described [ 12 , 13 ]. Briefly, gingival tissue corresponding to the extraction site was punched, and a 0.3-mm-diameter and 1.0-mm-depth hole was drilled in alveolar bone.…”
Section: Methodsmentioning
confidence: 99%
“…This eventually activates the transcription factor NF-κB, which regulates a large range of cytokines, including IL-1β, TNF-α, and RANK L/OPG; many of them have been shown to play a pathologic role in peri-implantitis [11]. In our previous studies, we have demonstrated that the TLR2/4 signaling pathway is aberrantly upregulated in many tissues in diabetic animals, which has been associated with the increase of pro-inflammatory factors in these tissues [11][12][13]. Notably, the inhibition of the TLR2/4 signaling pathway decreases the levels of such inflammatory cytokines in diabetic animals, indicating a causative relationship between TLR2/4 and inflammation in diabetes [13].…”
Section: Introductionmentioning
confidence: 96%